2006
DOI: 10.1097/00004728-200605000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of Multislice CT Angiography and MR Angiography in Assessing the Degree of Carotid Artery Stenosis in Consideration of Different Methods of Postprocessing

Abstract: CTA and MRA had a feasible agreement in measuring the degree of stenosis of the carotid arteries. The best result could be obtained for the evaluation of the RD and the NASCET method. In this case one has to take into account a systematic overestimation of CTA of 1.9%. The combination with an additional reconstructive postprocessing procedure did not improve the result but might be useful for the radiologist to identify the location of the closest narrowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The correlation of a semiautomated stenosis assessment with MRA of 56 ICAs was performed by Hackländer et al 13 Scherl et al 12 validated their approach on a small set of 10 ICAs. The accuracy of a semiautomated method was assessed by the comparison with consensus reading using axial and curved multiplanar plane reformatting images of 46 patients by Bucek et al 9 Wintermark et al 10 used a larger patient group of 125 patients for their validation, but because most of the patients in this study had no neurologic indications, a large part of their patient group showed no significant stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation of a semiautomated stenosis assessment with MRA of 56 ICAs was performed by Hackländer et al 13 Scherl et al 12 validated their approach on a small set of 10 ICAs. The accuracy of a semiautomated method was assessed by the comparison with consensus reading using axial and curved multiplanar plane reformatting images of 46 patients by Bucek et al 9 Wintermark et al 10 used a larger patient group of 125 patients for their validation, but because most of the patients in this study had no neurologic indications, a large part of their patient group showed no significant stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The potential advantages of such a system, such as the acceleration of measurements and reduced interobserver variability, have been widely acknowledged; however, the diagnostic value has not been sufficiently determined. Several studies have shown excellent intra-and interobserver variability, [7][8][9][10][11][12][13] yet the diagnostic accuracy and the cause of deviations of semiautomatic measurements have received little attention.…”
mentioning
confidence: 99%
“…Hacklaender et al [16] compared CTA and MRA including dependency of the chosen post-processing procedure. The software tested included semiautomatic vessel centerline extraction and threshold-based contour segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Hacklaender et.al. [16] noticed that the post-processing procedure did not improve the result, but might be useful to assist the radiologist in identifying the location of the greatest narrowing.…”
Section: Introductionmentioning
confidence: 99%
“…Modern multisection systems generate highly reproducible results, and multidimensional analysis of stenosis and plaque can be performed. [10][11][12] However, MR imaging can provide functional data (flow measurements, time-resolved imaging) and morphologic data (assessment of the vessel wall and lumen) without exposing the patient to radiation or iodinated contrast material. A variety of different MRA techniques has been reported, notably TOF-MRA and CE-MRA.…”
Section: Discussionmentioning
confidence: 99%